Thermal and Powder X-ray Diffraction Studies of Copper(II) Complexes of Schiff Bases - More, P.G.; Bhalvankar, R.B. (Asian Journal of Chemistry, 2010)
Copper(II) complexes (CuL2) of the Schiff bases (LH) derived from 4-phenyl-2-aminothiazole and o-hydroxyaldehydes have been, characterized by thermogravimetric analysis and powder X-ray diffraction studies. The TG curves are critically analysed to evaluate the various methods such as Freeman-Carroll, Coats-Redfern, MacCallum- Tanner, Horowitz-Metzger and Zsako. The values of kinetic parameters calculated by these methods are in good mutual agreement. A tetragonal crystal system is proposed on the basis of X-ray diffraction studies. Various X-ray parameters (lattice parameters, volume of unit cell and particle size) are calculated.